Integrated Effects of Warming Irrigation, Aeration, and Humic Acid on Yield, Quality, and GHG Emissions in Processing Tomatoes in Xinjiang - Chubo Wang; Yuhang Lu; Libing Song; Jingcheng Wang; Yan Zhu; Jiaying Ma; Jiliang Zheng (Agronomy)
Agricultural greenhouse gas emissions continue to rise year after year, contributing significantly to global warming—an escalating crisis that demands urgent attention. In order to address this issue, it is crucial to investigate the relationship between greenhouse gas emissions from farmland and crop yield and quality through comprehensive regulation of the soil micro-environment by inputting water, fertilizer, gas, and heat. Therefore, we conducted field experiments in 2024 to examine the effects of different water, fertilizer, gas, and heat conditions on the yield, quality, greenhouse gas emissions, net global warming potential (NGWP), and greenhouse gas emission intensity (GHGI) of processing tomatoes in Xinjiang, China. This study established two irrigation water temperatures (T0: the local irrigation water temperature, approximately 10–15 °C; and T1: warming irrigation, 20–25 °C), two humic acid application rates (H0: 0% and H1: 0.5%, % as a percentage of total fertilizer application), and three aeration methods (A0: no aeration, A1: Venturi aerated, and A2: micro–nano aerated) during the growth period. The results showed that the number of fruits per hectare (NP), vitamin C (VC) content, titratable acidity and lycopene content were all significantly increased with increasing temperature, application of 0.5% humic acid, and aeration. Warming has little effect on GHGI, while humic acid application and aeration have significant and extremely significant effects on GHGI. The GHGI of humic acid treatment was 7.70% lower than that of H0, and the GHGI of micro–nano aeration and Venturi aeration treatment was 18.95% and 6.85% lower than that of A0, respectively. We employed a comprehensive evaluation model that focused on overall differences to assess yield, quality, economic benefits, and environmental impact (GHGI, global warming potential). The optimal strategy identified comprised 20–25 °C irrigation, micro–nano aeration, and 0.5% humic acid, which collectively achieved the highest scores in yield, quality, and emission reduction. This study establishes a theoretical and technical foundation for the sustainable and efficient production of tomatoes in the arid regions of Northern Xinjiang.